2018
DOI: 10.1159/000493940
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gene Expression Pattern of Subjects with Completed Suicide and Comorbid Substance Use Disorder

Abstract: Background/Aim: Although individuals with substance use disorder (SUD) are at high risk of committing suicide, most studies of postmortem gene expression exclude subjects with SUD due to the potential confounding effect of drugs in the transcriptome. Thus, little is known about the gene expression profile in suicides with SUD. The identification of altered biological processes in suicides with SUD is crucial in the comprehension of the interaction between both pathologies. Methods: We evaluated the gene expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…in the process closely related to rDNA activity [9][10][11]. Correspondingly, different expression of genes related to the formation of neuronal processes has been observed in the PFC of male compared to female suicide completers [42,43]. However, the small sample size of female subjects may lead to an underpowered analysis and there is a chance of false negative results.…”
Section: Discussionmentioning
confidence: 99%
“…in the process closely related to rDNA activity [9][10][11]. Correspondingly, different expression of genes related to the formation of neuronal processes has been observed in the PFC of male compared to female suicide completers [42,43]. However, the small sample size of female subjects may lead to an underpowered analysis and there is a chance of false negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Hemimegaloencephaly with pachygyria [ 22 ] and focal cortical dysplasia with abnormal sulcation [ 23 ] were observed in patients with PTEN mutations. The incidence of cortical dysplasia in humans suggests that the PTEN gene is involved in neuronal migration [ 24 ]. Prominent multifocal cortical dysplasia was present in our case at 18–20 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, if we assume that all cells are homozygous, early fetal demise may occur in early pregnancy. It was reported that mice with homozygous PTEN loss died before embryonic day 7.5, since the tissue could not appropriately differentiate into three germ layers of endoderm, mesoderm, and ectoderm, while mice with the heterozygous mutated PTEN allele were viable and showed neuronal proliferation during brain development [ 24 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study was approved by the Ethical Committee for Human Research at the National Institute of Genomic Medicine and the Bioethics Committee of the Faculty of Medicine at the National Autonomous University of Mexico (UNAM). Tissue samples from the dorsolateral prefrontal cortex (Brodmann area 9) were sectioned during an autopsy protocol, following a previously described procedure 30 . Samples were stored in RNAlater at -80°C until their use.…”
Section: Samplesmentioning
confidence: 99%